Get ‘em While They’re Young: Complex Digitally-Mediated Tasks for EFL Learners in Primary Schools - Caruso, Celestine; Hofmann, Judith; Rohde, Andreas (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
We suggest that complex tasks can be introduced to learners as early as primary school level with the help of digital media in the form of different apps. As a theoretical basis, we will first outline the principles of teaching English in (German) primary schools. Secondly, we will look at the framework of Task-Based Language Teaching (TBLT) according to Nunan (2004) and explore how digitally-mediated tasks can be connected to this framework. Then, we will look at complex tasks as outlined by Hallet (2011) and present an example of a complex digital task for young English as a Foreign Language (EFL) learners that we developed and tested in a German primary school classroom. It is suggested that TBLT at the primary level is a motivating alternative to playful teaching techniques traditionally championed at the primary level. Moreover, it may be a way of bridging the problematic gap between the primary and secondary levels as tasks can prepare young learners for the challenges they will face at the secondary level.